Overview of the EDEN ISS Project. Mobile Test Facility: Analogue Testing of Plant Cultivation - Schubert, Daniel; Bamsey, Matthew; Zeidler, Conrad; Zabel, Paul; Vrakking, Vincent; Boscheri, Giorgio; Kohlberg, Eberhard (2018)
Plant cultivation in closed environments is challenging and several key technologies necessary for space-based plant production are not yet space-qualified or remain in early stages of development. The European-funded Horizon H2020 EDEN ISS project has the goal to develop and demonstrate higher plant cultivation technologies and procedures, suitable for future deployment on the International Space Station and from a long-term perspective, within Moon and Mars habitats. Over the last four years, the EDEN ISS consortium designed and tested essential plant cultivation technologies using an International Standard Payload Rack cultivation system for potential testing on-board the International Space Station. Furthermore, a Future Exploration Greenhouse was designed with the focus on future planetary bio-regenerative life support system deployments. A dedicated greenhouse system, called the Mobile Test Facility, was designed, built and deployed to the German Neumayer III research station in Antarctica. In Addition to producing biomass that will be returned to partner laboratories for analysis the facility provides the overwintering crew of 10 people with fresh vegetables during their isolation phase. The presentation gives an overview of the EDEN ISS research objectives, associated milestones and reports on the status of the analogue mission in Antarctica. In addition, the designed and implemented subsystems are described. Further, an overview of the assembly, integration, and test phase that took place in 2017 at the DLR Institute of Space Systems is given.